Longitudinal assessment of lung function in children with sickle cell disease. Issue 7 (22nd December 2015) - Lunt, Alan; McGhee, Emily; Sylvester, Karl; Rafferty, Gerrard; Dick, Moira; Rees, David; Height, Susan; Thein, Swee Lay; Greenough, Anne
Summary: Objectives: To prospectively assess longitudinal lung function in children with sickle cell disease (SCD). Working hypothesis: Lung function in SCD children deteriorates with increasing age and the decline is more marked in younger children who have recently suffered ACS episodes. Study design: Two prospective longitudinal studies. Patient‐subject selection: Two cohorts of SCD children and age and ethnic matched controls were recruited. Cohort One (47 SCD and 26 controls) had a median age of 8.8 years and follow up of 2 years and Cohort Two (45 SCD and 26 controls) a median age of 10.2 years and follow up of 10 years. Methodology: Forced expiratory volume in one second (FEV1 ), vital capacity (VC), forced expiratory flow between 25% and 75% of VC (FEF25–75 ), total lung capacity (TLC) and residual volume (RV) were measured on two occasions. Results: In both groups of SCD children, lung function declined significantly, but in neither control group. ACS episodes were more frequent during the follow up period in Cohort One than Cohort Two ( P < 0.0001). The rate of decline was greater in Cohort One than Cohort Two for FEV1 ( P = 0.008), VC ( P = 0.001), FEF25–75 ( P = 0.030), TLC ( P = 0.004), and RV ( P = 0.043). In Cohort Two restrictive abnormalities were more common at follow up ( P = 0.006). Conclusions: Lung function deteriorated with increasing age in SCD children and the rate of decline was greater in younger children in whom ACS episodes were more common.Pediatr Pulmonol. 2016;51:717–723 . © 2015 Wiley Periodicals, Inc.